Infections with the ascomycete fungus Metschnikowia typographi sp.nov. in the bark beetles Ips typographus and Ips amitinus (Coleoptera, Scolytidae) - Weiser, J; Wegensteiner, R; Händel, U; Zizka, Z (Folia microbiologica, 2003)
The ascomycete fungus Metschnikowia typographi sp.nov. is described. It infects the spruce bark beetles Ips typographus L. and Ips amitinus Eichl. Masses of vegetative cells and navicular asci (I. typographus 13-17 x 2 microns; I. amitinus 17-22 x 2 microns) were found in cells of the midgut epithelium and in the body cavity of infected beetles. Each ascus contains two needle-shaped ascospores flattened in the central part, 0.5-1.5 x 0.3 x 13-15 microns and pointed at both ends. The parasitic species of Metschnikowia, M. bicuspidata, M. artemiae, M. unicuspidata, M. wickerhami and M. typographi are discussed as a special group of the genus characterized by morphological characters.
Keywords: brouci; Spores, Fungal; Ascomycota; prevalence; Prevalence; smrk; mykózy; zvířata; Coleoptera; Picea; Mycoses; spory hub; Animals